Applicant Fairness Perceptions of a Robot-Mediated Job Interview: A Video Vignette-Based Experimental Survey - Nørskov, Sladjana; Damholdt, Malene F.; Ulhøi, John P.; Jensen, Morten B.; Ess, Charles; Seibt, Johanna (Frontiers in Robotics and AI, 2020)
It is well established in the literature that biases can occur during the employment interview and that applicants' fairness perception related to selection procedures can influence attitudes, intentions, and behaviors toward the recruiting organization. This study explores how social robotics may affect this situation. Based on an experimental survey (n=235), the study examines applicant fairness perceptions of two types of job interviews: a face-to-face and a robot-mediated interview. In the robot-mediated interview, two teleoperated robots are used as fair proxies for the applicant and the interviewer, thus providing symmetrical visual anonymity unlike prior research that relied on asymmetrical anonymity. This setup is intended to eliminate visual cues that typically cause implicit biases and discrimination of applicants, but also to prevent biasing the interviewer's assessment through impression management tactics typically used by applicants. The study finds, contrary to our expectations, that the face-to-face interview is perceived as fairer. We discuss this finding and its implications, and conclude by addressing future research avenues.